Glucocorticoid-Induced Bone Fragility Is Prevented in Female Mice by Blocking Pyk2/Anoikis Signaling - Sato, Amy Y (Endocrinology, 2019)
Excess of glucocorticoids (GCs) is a leading cause of bone fragility, and therapeutic targets are sorely needed. We report that genetic deletion or pharmacological inhibition of proline-rich tyrosine kinase 2 (Pyk2) prevents GC-induced bone loss by overriding GC effects of detachment-induced bone cell apoptosis (anoikis). In wild-type or vehicle-treated mice, GCs either prevented osteoclast apoptosis or promoted osteoblast/osteocyte apoptosis. In contrast, mice lacking Pyk2 [knockout (KO)] or treated with Pyk2 kinase inhibitor PF-431396 (PF) were protected. KO or PF-treated mice were also protected from GC-induced bone resorption, microarchitecture deterioration, and weakening of biomechanical properties. In KO and PF-treated mice, GC increased osteoclasts in bone and circulating tartrate-resistant acid phosphatase form 5b, an index of osteoclast number. However, bone surfaces covered by osteoclasts and circulating C-terminal telopeptides of type I collagen, an index of osteoclast function, were not increased. The mismatch between osteoclast number vs function induced by Pyk2 deficiency/inhibition was due to osteoclast detachment and anoikis. Further, GC prolongation of osteoclast lifespan was absent in KO and PF-treated osteoclasts, demonstrating Pyk2 as an intrinsic osteoclast-survival regulator. Circumventing Pyk2 activation preserves skeletal integrity by preventing GC effects on bone cell survival (proapoptotic for osteoblasts/osteocytes, antiapoptotic for osteoclasts) and GC-induced bone resorption. Thus, Pyk2/anoikis signaling as a therapeutic target for GC-induced osteoporosis.